2017
DOI: 10.9734/jalsi/2017/32402
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Botanicals and Chemicals to Control Cercospora Leaf Spot Disease of Country Bean in Field Condition

Abstract: to estimate the control measure of cercospora leaf spot disease of country bean. Before sowing, the seeds were treated with six different treatments like as Tı: Autostin 50 WP, T 2 : Aimcozim 50 WP, T 3 : Ata leaf extract (1:2 w/v), T 4 : Neem leaf extract (1:2 w/v), T 5 : Biskatali leaf extract (1:2 w/v) and T 6 : Mahogani leaf extract (1:2 w/v). The experiment was laid out in Randomized Complete Block Design (RCBD) with three replications. In field condition, similar four leaf extracts and two chemicals were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Dey et al [24] found that spraying a 0.2% ). Plots receiving mancozeb and tridemorph plus maneb exhibited the best overall disease control and higher yields, followed by copper oxychloride [25] Bagwan [26] reported that Thiram (0.2%), Copper oxychloride (0.2%), and Mancozeb (0.2%) are compatible with Trichoderma harzianum and Trichoderma viride.…”
Section: Conventional Disease Manage-mentmentioning
confidence: 99%
“…Dey et al [24] found that spraying a 0.2% ). Plots receiving mancozeb and tridemorph plus maneb exhibited the best overall disease control and higher yields, followed by copper oxychloride [25] Bagwan [26] reported that Thiram (0.2%), Copper oxychloride (0.2%), and Mancozeb (0.2%) are compatible with Trichoderma harzianum and Trichoderma viride.…”
Section: Conventional Disease Manage-mentmentioning
confidence: 99%
“…Management: Cercospora leaf spot affects the majority of commercial cultivars, and the severity of the disease is strongly linked to faba bean rotations. Planting disease-free seed, resistant cultivar and use of botanicals (neem leaf extract, Biskatali leaf extracts, Arjun leaves extract, Debdaru leaves extract, garlic cloves extract) are quite effective in controlling Cercospora leaf spot of country bean (Dey et al, 2017;Uddin, 2013). Recent findings have shown that early applications of carbendazim, tebuconazole, chlorothalonil, and triadimefon are the most effective fungicide control strategies (Kimber, 2011).…”
Section: Cercospora Leaf Spotmentioning
confidence: 99%